Microfacies and depositional environment of Bajawan and Baba Formations in Kirkuk Oil fields north Iraq - Hawazen N. Farhan; Lafta S. Kadem; Qahtan A. Mohammed (Tikrit Journal of Pure Science)
The study of six selected wells from Kirkuk oil field petrographic and physical properties ; investigation while leads to interpret the microfacies and environment for Bajawan and Baba Formations. Five carbonate microfacies distingished from Bajawan Formation ( Lime Mudstone Microfacies, Fossiliferous Lime Wackstone Microfacies, Miliolid Packstone Microfacies, Miliolid Grainstone Microfacies and Coral, Boundstone microfacies ), while Two microfacies described from Baba Formation (Limestone  bearing Larger foraminifera (Lepidocylina- Nummulites) packstone-wackstone microfacies and Fossiliferous  Floatstone bearing Larger Foraminifera  microfacies ).